Interaction between Perceived Action and Music Sequences in the Left Prefrontal Area - Wakita, Masumi (Frontiers in Human Neuroscience, 2016)
Observing another person’s piano play and listening to a melody interact with the observer’s execution of piano play. This interaction is thought to occur because the execution of musical-action and the perception of both musical-action and musical-sound share a common representation in which the frontoparietal network is involved. However, it is unclear whether the perceptions of observed piano play and listened musical sound use a common neural resource. The present study used near-infrared spectroscopy to determine whether the interaction between the perception of musical-action and musical-sound sequences appear in the left prefrontal area. Measurements were obtained while participants watched videos that featured hands playing familiar melodies on a piano keyboard. Hand movements were paired with either a congruent or an incongruent melody. Two groups of participants (nine well-trained and nine less-trained) were instructed to identify the melody according to hand movements and to ignore the accompanying auditory track. Increased cortical activation was detected in the well-trained participants when hand movements were paired with incongruent melodies. Therefore, an interference effect was detected regarding the processing of action and sound sequences, indicating that musical-action sequences may be perceived with a representation that is also used for the perception of musical-sound sequences. However, in less-trained participants, such a contrast was not detected between conditions despite both groups featuring comparable key-touch reading abilities. Therefore, the current results imply that the left prefrontal area is involved in translating temporally structured sequences between domains. Additionally, expertise may be a crucial factor underlying this translation.